THE SYSTEMATICITY OF SOLUTIONS FOR EXPANDING THE PRODUCTION OF HIGH-QUALITY PRODUCTS BY AN EXPORT-ORIENTED METALLURGICAL ENTERPRISE - KHOMENKO, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study outlines the approaches toward the rationalization of the technological process of pellet production by combining iron ore extraction in the quarry, its milling, concentrate enrichment, pellet firing. The practice of system implementation of modern technology of flotation processing of iron content into the concentrate as a strategic task of improving the quality of pellets is described.The peculiarities of involving a significant percentage of "low-grade" ores in production in case of necessity are revealed. It was concluded that the implementation and successful functioning of the quality management system are affected by engineering mistakes, poor cooperation with suppliers, the return of low-quality products to the enterprise, additional transportation expenses.  The sequence of development of the fundamental documents of the quality management system regarding the implementation of the policy in the field of expansion of export supplies of pellets and improvement of the organizational structure of the company's management is covered.The iron content in pellets was predicted using the auto regression model. An improved structure of management of foreign economic activity in case of the implementation of the project on additional production of high-quality pellets is proposed. The costs for increasing the volume of production of iron ore raw materials for the project for the successful functioning of the automated management system for the entire technological process of charge preparation, pelletizing and firing of pellets are systematically defined.A risk assessment was carried out in conditions of implementation of the model for calculating the capital assets of the complex of equipment for the production of high-quality pellets of a well-known global company. Decisions regarding the positioning of the plant's pellets on the world market with determination of the pricing strategy are justified.
Keywords: production; pellets; competition; quality; export deliveries; prices